Peningkatan Motivasi dan keterampilan Berbicara Berbantu Kotak Kejutan - Panjaitan, Chery Julida (JURNAL PENA EDUKASI, 2021)
Abstract: Online learning has the effect of decreasing student motivation and learning outcomes in the new normal era at MIS Al Asriyah Langsa. The awkwardness of interacting with teachers and other students results in a lack of motivation to learn optimally. Good response from friends also decreased. In addition, teachers are less optimal in using interesting learning media because of limited time. As a result, they are reluctant to express ideas when required to explain the subject matter. For this reason, this study aims to improve students' motivation and speaking skills with the help of surprise boxes in fifth grade students of MIS Al Asriyah Langsa for the 2020/2021 academic year. This study uses a CAR approach with two cycles. To collect data, the researcher used observation, interviews, and oral tests. The results of the research in the first cycle showed that the students' learning motivation was 56.25% and speaking skills were 31.25%. Learning motivation increased to 75% and students' ability to express ideas became 81.25%. These results indicate an increase in learning motivation as much as 18.75% and an increase in speaking skills by 50%. Thus, it can be concluded that the surprise box media was able to increase the learning motivation and speaking skills of the fifth grade students of MIS Al Asriyah Langsa. Keywords: learning motivation, speaking skill, surprise box  Abstrak: Pembelajaran daring membawa pengaruh menurunnya motivasi dan hasil belajar siswa pada era new normal di MIS Al Ashriyah Langsa. Kecanggungan berinteraksi dengan guru dan siswa lainnya berakibat kurangnya dorongan untuk belajar dengan optimal. Respon baik dari teman juga menurun. Selain itu, guru kurang maksimal memanfaatkan media pembelajaran yang menarik karena waktu yang terbatas.  Akibatnya, mereka enggan menuangkan gagasan ketika dituntut memaparkan materi pelajaran. Untuk itulah, penelitian ini bertujuan meningkatkan motivasi dan keterampilan berbicara siswa berbantu kotak kejutan pada siswa kelas V MIS Al Ashriyah Langsa tahun ajaran 2020/2021. Penelitian ini menggunakan pendekatan PTK dengan dua siklus. Untuk menarik data, peneliti menggunakan observasi, wawancara, dan tes lisan. Hasil penelitian pada siklus I diketahui motivasi belajar siswa sebesar 56,25% dan keterampilan berbicara sebesar 31,25%. Motivasi belajar meningkat menjadi 75% dan kemampuan menuangkan ide siswa menjadi 81,25%. Hasil tersebut menunjukkan terjadi peningkatan motivasi belajar sebanyak 18,75% dan peningkatan keterampilan berbicara sebesar 50%. Denagn demikian, dapat disimpulkan bahwa media kotak kejutan mampu meningkatkan motivasi belajar dan keterampilan berbicara siswa kelas V MIS Al Ashriyah Langsa. Kata kunci: motivasi belajar, keterampilan berbicara, kotak kejutan